Cross- Border Union Alliances and Transnational Collective Bargaining: A Case Study in a Canadian MNC - Hennebert, Marc- Antonin (Just Labour, 2011)
The last two decades have seen an emergence of new forms of international employee representation within multinational corporations (MNCs). In EU member states, the management at MNCs find themselves having to deal with statutory European Works Councils (EWCs) while at a more global level some studies show a multiplication of solidarity network s and cross-border union alliances put in place by reinvigorated Global Union Federations (GUFs). In order to evaluate the extent to which these cross-border alliances can support the development of transnational collective bargaining within MNCs, this article draws on a single case study conducted recently in a Canadian MNC in the commercial printing industry, namely Quebecor World Inc. In recent years, before the dismantling of this Canadian multinational, union officials sought to coordinate the various unions in this company internationally and to open up a new space for collective bargaining at the transnational level by negotiating an international framework agreement with its management.